How to improve sixth graders’ reading comprehension through the skimming technique (2007)
This project was developed at Venecia school morning shift located in Tunjuelito, Zone 6 in Bogotá. Population involved consisted of forty-four, sixth-grade students. The pupils were between 11-13 years old, whose social and economic conditions were difficult. Our goal for this project was to introduce the skimming technique to familiarize students with it to make the reading process easier since reading in a foreign language implies a complex process and students need useful tools to confront a text in an effective way. Through different reading workshops worked in classes we discovered that reading can be a meaningful and interesting process for students. According to the findings, we concluded that the skimming technique was very easy to apply and it was appropriate for reading and comprehending a text. Key words: Skimming technique, meaningful reading, innovation Este proyecto se desarrolló en el Colegio Venecia Institución Educativa Distrital, jornada mañana, localidad 6 de Tunjuelito en Bogotá (Colombia). Los estudiantes que participaron en el proyecto cursaban grado sexto. Tenían entre 11 y 13 años de edad y vivían en condiciones económicas y sociales difíciles. Puesto que el proceso de lectura es complejo y los estudiantes necesitan herramientas útiles para enfrentarse a un texto de manera exitosa, nuestro objetivo fue familiarizar a los estudiantes con el uso de la técnica del vistazo, de tal manera que el proceso lector fuera más fácil. A través de diferentes talleres de lectura trabajados en clase, descubrimos que la lectura puede ser un proceso significativo e interesante para los estudiantes. De acuerdo con los hallazgos concluimos que la técnica del vistazo fue apropiada y fácil de aplicar para leer y entender un texto. Palabras clave: Técnica del vistazo, lectura significativa, innovación